Suture looping technique for coracoclavicular fixation biomechanically outperforms fixation constructs utilizing either a metallic anchor or an all-suture anchor - Hao-Ming Chang; Shih-Ting Lin; Chi-Hsiu Wang; Yu-Meng Hsiao; Kai-Lan Hsu; Fa-Chuan Kuan; Wei-Ren Su; Chih-Kai Hong (Journal of Orthopaedic Surgery)
Background The utilization of all-suture anchors in coracoclavicular (CC) suture fixations offers satisfactory clinical advantages. This study aimed to compare the biomechanical properties of suture looping, conventional metallic anchors, and all-suture anchors in CC suture fixation in a synthetic bone model. Hypothesis Suture looping for CC fixation would result in smaller cyclic elongation and greater ultimate pull-out strength than suture anchor techniques. Methods A total of 27 composite scapula were divided into three groups: suture looping group (group L), metallic anchor group (group M), and all-suture anchor group (group A). In group L, two No. 2 braided sutures were looped into the coracoid base for CC fixation. In groups M and A, 5.0 mm metallic suture anchors and 2.8 mm all-suture anchors were used, respectively. Prepared specimens were secured using a material testing machine. Each specimen was tested with a preload between 0 and 20 N for 10 cycles, cyclic loading between 20 and 70 N for 1000 cycles, and final loading to failure. Cyclic elongation, linear stiffness, ultimate load, and failure modes were recorded. Results All the specimens were subjected to cyclic loading tests. Elongation after cyclic loading in group L (1.0 ± 0.2 mm) was significantly smaller than that in groups M (1.4 ± 0.2 mm) ( p = .002) and A (2.5 ± 1.1 mm) ( p < .001). Cyclic elongation in group M was also significantly lower than that in group A ( p = .004). Ultimate failure load in group L (472 ± 53 N) was significantly greater than that in group M (380 ± 35 N) ( p = .002) and A (354 ± 94 N) ( p = .010). Suture rupture was the most common failure pattern in group L, whereas two specimens failed because of a coracoid fracture. Both suture rupture and anchor pull-out were common in groups M and A. Conclusions The suture looping technique in CC fixation provides a significantly smaller cyclic displacement and greater ultimate failure load than metallic and all-suture anchors. The clinical relevance is that smaller cyclic elongation and greater ultimate failure load imply a reduced risk of fixation construct failure.